Foreign Institutional Investors and their impact on Auto and Bank index Volatility-An Empirical Study (Journal of Finance, Business and Management Studies, 2024)
In Indian stock Market, Foreign Institutional Investors (FIIs) have been a significant regarded as a key source of stock market volatility. The impact research of stock market returns and the FIIs inflows and outflows link was established to determine the impact between FIIs portfolio flows and stock market volatility. The purpose of this paper is to assess the investing practices of (FIIs) and its relationship to stock market returns in India. The ADF unit root test and Arch family models were used to collect and analyse monthly data from January 2006 to December 2021. The data is stationarity at level, according to the results of the Unit root test. After applying the GARCH test analysis, it was found that the volatility of the Indian stock market is affected by prior time periods volatility and that FIIs' investments play a substantial role in the volatility of the NIFTY and S&P BSE indices. The foreign institutional investments are influencing the volatility of Nifty Auto, Nifty Bank, S&P BSE Auto and S&P BSE Bank.